Faktor-faktor yang Mempengaruhi Minat Beli Ulang Green Product Starbucks - Putra, Dicky Ramadhan; Prasetyawati, Yuliana Riana (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2021)
The growth of coffee consumption in the community has a negative impact on the increase in the amount of plastic waste from coffee drinks. This condition is the focus of Starbuck's attention to produce green product reusable Color changing cups. Therefore, this study aims to determine the factors that influence buying interest in green product reusable color changing cups. The research method used is survey and the data analysis technique used is path analysis. Primary data was obtained through a questionnaire distributed to 80 respondents who are Instagram followers @starbucksindonesia who use reusable color changing cups at the Sahid Sudirman Center. The results showed that Green Product had a positive effect on repurchase intention through green advertising. This research also shows that the innovation of reusable color changing cups as a green product launched by Starbucks, was received positively and in accordance with the needs of people who have started to care about environmentally friendly products. Starbucks consumers will reuse reusable color changing cups as containers or glasses when purchasing drinks.